Work Based Learning in Vocational Education Training (VET): A Review of Engagement Among Stakeholders - Mohammad Ammalluddin Ramli,; Siti Hajar binti Zakariah,; Fazlinda binti Ab Halim, (Online Journal for TVET Practitioners, 2024)
To improve the implementation of the programme, an integrated approach is required as stakeholder involvement is a critical factor that needs to be taken into account. In order to improve the capacity of the WBL programme through stakeholder engagement, this paper addresses the literature on stakeholder perspectives on WBL. The perspectives of the three main stakeholders, namely industry, students, and higher education institutions, were explored in this paper. This review paper adhered to the standards of the GEA-RIME committee for systematic literature reviews. Based on the research questions, this paper explored different types of WBL models and how stakeholders engage with each WBL model, as well as the challenges stakeholders face during the engagement. For the final literature papers evaluation and findings, 37 publications on in-service learning in hospitality and tourism curricula published between 2010 and 2022 were selected. The results of the literature review show that there are many types of WBL models, each with a different approach to stakeholder engagement and different challenges. It can be concluded that strong multi-stakeholder engagement is crucial and key for effective WBL training transfer. Based on the findings, it is recommended that all stakeholders should share the responsibility to ensure that the transfer of knowledge and skills during the WBL process achieves the quality standards of training and produces the highly skilled graduates desired by the industry.